Pierwotne brzmienie tekstu? Refleksje nad krytyką tekstualną Biblii - Lipiński, Edward (The Biblical Annals, 2016)
The textual criticism of the Bible, as viewed traditionally, has for its primary object the reconstruction of the original text from manuscript versions and quotations in ancient writings. Since biblical texts have been often expanded and changed in Antiquity, it is not evident what one should regard as original version. Therefore, the scientific object of textual criticism is to trace the history of the text, to identify and characterize its various recensions or adaptations. This is done in the article by examining a few cases in order to illustrate various kinds of intentional changes or developments and of accidental errors, which happened most often in foreign words, place-names, and personal names. Besides, the same consonantal texts can sometimes be understood in different ways, the masoretic vocalization being one of these interpretations